Use of Augmentative and Alternative Communication by Individuals with Rett Syndrome Part 2: High-Tech and Low-Tech Modalities - Unholz-Bowden, Emily K.; Girtler, Shawn N.; Shipchandler, Alefyah; Kolb, Rebecca L.; McComas, Jennifer J. (Journal of developmental and physical disabilities, 2024)
The vast majority of individuals with Rett syndrome do not utilize natural speech and therefore require alternative and augmentative communication (AAC). The purpose of the current study was to investigate the use of high- and low-tech AAC modalities by three individuals with Rett syndrome given similar instruction for using both modalities. For all participants, the number of sessions to criterion and cumulative number of trials with independent requests during simultaneous or alternating instruction in the use of a high- and low-tech AAC modality were investigated. Parents conducted all sessions with remote coaching from a research assistant via telecommunication. Each participant exhibited idiosyncratic response patterns in terms of use of their high- and low-tech AAC modalities during instruction but ultimately demonstrated the ability to use both modalities to make requests. Implications for future research and practice pertaining to AAC of individuals with complex communication needs are discussed. This paper is a companion to Girtler et al. ( 2023 ).